Enhancing the Competitiveness of Indonesian MSME Products in Malaysia Through Simple Supply Chain Management Strategies - Sapto Supriyanto; Bambang Guritno; Samtono Samtono; Anna Srilestari M; Putria Sri Handayani (An International Journal Tourism and Community Review, 2025)
This study investigates the implementation of a simple supply chain strengthening program to enhance the competitiveness of Indonesian micro, small, and medium enterprises (MSMEs) in the Malaysian market. Indonesian MSMEs face challenges in market entry, including limited knowledge of export procedures, high distribution costs, and low product acceptance due to labeling and packaging issues. The research aims to evaluate whether targeted, low-cost interventions can improve MSME readiness and performance in international trade. A total of 40 MSMEs from the food and beverage, handicraft, and processed product sectors participated, with 55 owners, managers, and employees engaged in training and mentoring activities. Data were collected using pre–post knowledge questionnaires, logistics cost records, product placement monitoring, in-depth interviews, and focus group discussions. The program resulted in a 35% increase in knowledge scores, a 15% reduction in average distribution costs, a rise in product acceptance from 45% to 72%, and successful distribution partnerships for 8 MSMEs, leading to a 180% increase in monthly orders. The findings indicate that practice-based, contextual training combined with logistics optimization and market facilitation significantly enhances MSME competitiveness. Low-cost interventions are shown to be effective and scalable, providing practical guidance for policymakers and support institutions. The study contributes to the literature on MSME export readiness by demonstrating that structured, simple supply chain strategies can deliver measurable outcomes in low-resource settings. Future research should examine larger samples, longer monitoring periods, and additional markets to assess long-term sustainability and sector-specific strategies